Multiliteracy in the Millennial Generation: A Case Study of Political Cartoons on Instagram Tempodotco - Adi Fadhilah Nurul Rahman (PERSPEKTIF, 2022)
This article aims to explore how the millennial generation understands multimodal texts. The problem is focused on how readers construct real-world references from cartoons, narrate cartoons, interpret respondents' facial expressions depicted, understand the relationship between text and images, and build metaphorical relationships between fictional cartoon scenes and political arguments. The data were collected through interviews with six people who were selected by year of birth as the millennial generation category and follow tempodotco on Instagram, but came from different backgrounds, and this data was analyzed qualitatively. This study concludes that political cartooning is a fairly complex process and requires one to draw from different literacies. The millennial generation's experience with various related events also affects them in dealing with them and the reader's familiarity with the cartoon genre, knowledge of cultural symbols, and the experience of analytical thinking about events and situations in the real world are also factors that determine readers.